The execution of the green building project in klang valley, Malaysia: A pilot study - Isa, Nor Kalsum Mohd; Albahori, Ainul Samihah; Alias, Anuar; Ismail, Kamarul (Universiti Putra Malaysia, 2019)
Execution of the green building project specifically among the housing developers in Malaysia is still at its infancy. As of August 2016, there are only 16 housing projects certified by the Green Building Index (GBI) under the category of Residential New Construction (RNC) since the assessment systems established in 2010. The authors address this issue in the context of the factors affecting the execution of the green building project among the housing developers in Klang Valley. A pilot study by using questionnaire survey was conducted among 30 housing developers from 10 different zones divided by the Ministry of Housing and Local Government, Malaysia. This paper aimed to report the results of the reliability test of the designed questionnaire. The results based on the Cronbach’s Alpha analysis showed that the items used in the questionnaire were reliable and obtained an acceptable level of internal consistency, which were relevant for the main study. The pilot study revealed that only 9 out of 30 respondents had the completed or ongoing green building projects. The findings exposed the level of knowledge, emotion, value, attitude, behavior and the potential factors affecting the execution of the green building projects among the housing developers in Klang Valley. © Universiti Putra Malaysia Press.